2003
DOI: 10.4049/jimmunol.171.3.1156
|View full text |Cite
|
Sign up to set email alerts
|

The Immune Response Modifier and Toll-Like Receptor 7 Agonist S-27609 Selectively Induces IL-12 and TNF-α Production in CD11c+CD11b+CD8− Dendritic Cells

Abstract: IL-12 and TNF-α production by dendritic cells (DCs) is a critical step in the initiation of local inflammation and adaptive immune responses. We show in this study that a small molecule immune response modifier that is a Toll-like receptor 7 (TLR7) agonist induces IL-12 and TNF-α production from murine CD11c+CD11b+CD8− DCs, a subset not previously known for this activity. Stimulation of these DCs through TLR7 in vivo induces significant cytokine production even 12 h after initial stimulation, as well as migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
88
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 70 publications
7
88
1
Order By: Relevance
“…Subset-specific up-regulation of costimulatory molecules has been observed in other in vivo models, including after administration of ␣-galactoceramide or TLR ligands and during infection with certain parasites or viruses (11, 23, 25, 35-37). The differential capacities of DC subsets to up-regulate CD80, CD86, or CD40 in response to microbial infection could be due to differential expression of TLRs (5,38,39). However, TLR-deficient DC up-regulate costimulatory molecules as well as TLR-expressing DC in mixed bone marrow chimeras after administration of the TLR agonist (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subset-specific up-regulation of costimulatory molecules has been observed in other in vivo models, including after administration of ␣-galactoceramide or TLR ligands and during infection with certain parasites or viruses (11, 23, 25, 35-37). The differential capacities of DC subsets to up-regulate CD80, CD86, or CD40 in response to microbial infection could be due to differential expression of TLRs (5,38,39). However, TLR-deficient DC up-regulate costimulatory molecules as well as TLR-expressing DC in mixed bone marrow chimeras after administration of the TLR agonist (22).…”
Section: Discussionmentioning
confidence: 99%
“…Ϫ DC (23,38) despite differential TLR7 expression on these subsets detected at the mRNA level (38,39). Thus, the subset-specific up-regulation of costimulatory molecules could be dependent on a differential capacity of DC subsets to respond to proinflammatory cytokines (11), rather than a differential expression of TLRs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that the activation of NK cells by DC can provide an early source of IFN-␥ that is necessary for T H 1 responses (31). Similarly, the activation of innate immune response cells via TLR signaling can also provide help, in the form of inflammatory cytokines and DC activation, for Ag-specific T cell responses (26,28,(32)(33)(34)(35). Such activation of innate immune signaling may help overcome immune tolerance to self Ags (28,36,37) or disrupt regulatory T cell effects (38).…”
Section: Discussionmentioning
confidence: 99%
“…For example, murine DC subsets differentially express TLR7, and these expression patterns may result in subset-dependent responses after i.v. administration of TLR7/8 ligands such as the synthetic adjuvant resiquimod (R-848) [15,16]. With respect to migrating DC, especially their subsets, very little is known about expression of TLR and their response to specific TLR ligands in vivo.…”
Section: Introductionmentioning
confidence: 99%